The many saints of Newark [videorecording (DVD)] - Gandolfini, Michael; Bernthal, Jon; Farmiga, Vera; Magnussen, Billy, 1985- (Warner Bros. Entertainment Inc., 2021)
Young Anthony Soprano is growing up in one of the most tumultuous eras in Newark's history, becoming a man just as rival gangsters begin to rise and challenge the all-powerful DiMeo crime family's hold over the increasingly race-torn city. Caught up in the changing times is the uncle he idolizes, Dickie Moltisanti, who struggles to manage both his professional and personal responsibilities, and whose influence over his nephew will help make the impressionable teenager into the all-powerful mob boss later known as Tony Soprano.